Bionic hand as artificial organ: Current status and future perspectives. Issue 2 (19th February 2019) - Aman, Martin; Sporer, Matthias E.; Gstoettner, Clemens; Prahm, Cosima; Hofer, Christian; Mayr, Winfried; Farina, Dario; Aszmann, Oskar C.
Abstract: Even though the hand comprises only 1% of our body weight, about 30% of our central nervous systems (CNS) capacity is related to its control. The loss of a hand thus presents not only the loss of the most important tool allowing us to interact with our environment, but also leaves a dramatic sensory‐motor deficit that challenges our CNS. Reconstruction of hand function is therefore not only an essential part of restoring body integrity and functional wholeness but also closes the loop of our neural circuits diminishing phantom sensation and neural pain. If biology fails to restore meaningful function, today we can resort to complex mechatronic replacement that have functional capabilities that in some respects even outperform biological alternatives, such as hand transplantation. As with replantation and transplantations, the challenge of bionic replacement is connecting the target with the CNS to achieve natural and intuitive control. In recent years, we have developed a number of strategies to improve neural interfacing, signal extraction, interpretation and stable mechanical attachment that are important parts of our current research. This work gives an overview of recent advances in bionic reconstruction, surgical refinements over technological interfacing, skeletal fixation, and modern rehabilitation tools that allow quick integration of prosthetic replacement.